The Advancement of Islamic Literature and Libraries in Al-Andalus the Era UMMAYAD DYNASTY II - Ahsin, Kahfie Ahmad; Haniati, Umi; Shiddieqy, Fahmi Ash (UIN Raden Intan Lampung, 2025)
This article discusses the development of Islamic thought in the field of Islamic literature in Andalusia. Literature itself is a literary material that is usually used as a source of knowledge based on science that refers to intellectual development. This article will discuss literature during the Umayyad Dynasty II in Andalusia. This is intended to determine the development of Islamic thought in the field of literature, which has made a major contribution to the development of science itself. Without literature, technological developments may not be significant, but literature in Andalusia during the Umayyad dynasty had a glory that greatly influenced intellectual development among the community. The theory used in this article is the theory of civilization and science, with a historical approach that reveals past civilizations. The method used is the historical research method, namely: Heuristics, Verification, Interpretation, and Historiography. This article is qualitative in nature, with reference to the study of literature in collecting sources and information about literature during the Umayyad Dynasty in Andalusia. Keywords: Andalusia, Daulah Bani Ummayah, Literature, Development of Islamic Thought.